2022
DOI: 10.3389/fpsyg.2022.903142
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Processes Predicting Outbursts and Functional Impact in Misophonia

Abstract: Misophonia involves a decreased tolerance to certain sounds and is associated with a range of emotions and emotion processes. In addition to the distress caused by misophonia, some individuals report having aggressive outbursts and significant impact on doing things they would like to be able to do. This study aimed to examine whether misophonia-specific cognitive and emotional processes were associated with misophonic outbursts and impact, and whether these relationships could be explained in part by emotion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
(59 reference statements)
2
5
0
1
Order By: Relevance
“…However, it remains unclear why these sounds are annoying for so many people. The similarity in trigger sounds in both groups may imply cognitive and emotional processes involved in evaluating the stimuli to be key when trying to make a difference for those affected by misophonia ( 23 ). In the current study, the difference between functionally impaired and non-impaired groups rather lay in the intensity to which these stimuli were experienced and evaluated as annoying.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it remains unclear why these sounds are annoying for so many people. The similarity in trigger sounds in both groups may imply cognitive and emotional processes involved in evaluating the stimuli to be key when trying to make a difference for those affected by misophonia ( 23 ). In the current study, the difference between functionally impaired and non-impaired groups rather lay in the intensity to which these stimuli were experienced and evaluated as annoying.…”
Section: Discussionmentioning
confidence: 99%
“…Emotion regulation difficulties were reported to be associated with misophonia symptoms, even beyond the associations with depressive and anxiety symptoms ( 21 , 22 ). As both, the experienced emotions toward certain sounds and the appraisals of the emotional reaction (externalizing: blaming others; internalizing: blaming oneself), differ in individuals with versus without misophonia ( 23 ), a closer investigation of emotion regulation processes appears warranted. Many individuals report misophonic symptoms to occur with family members and/or significant others but not, or at least not to the same extent, to unfamiliar others.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported on the potential role of anxiety sensitivity in misophonia [58,59]. However, Wang and Vitoratou [60] proposed that this relationship could be explained by a shared overlap in anxiety symptoms rather than a unique contribution of anxiety sensitivity. More research is needed to investigate further the role of anxiety symptoms and sensitivity in misophonia.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported on the potential role of anxiety sensitivity in misophonia (Cusack et al, 2018;Dixon et al, 2023). However, Wang et al (2022) proposed that this relationship could be explained by a shared overlap in anxiety symptoms rather than a unique contribution of anxiety sensitivity. More research is needed to investigate further the role of anxiety symptoms and sensitivity in misophonia.…”
Section: Discussionmentioning
confidence: 99%